Kinetic and Mechanistic Study of the Oxidation of D-Mannose by Tetraethylammonium Chlorochromate in Aqueous Acetic Acid Medium - Tomar, Ashish; Kumar, Arun (Asian Journal of Chemistry, 2010)
The kinetic and mechanistic study of the oxidation of D-mannose by tetraethylammonium chlorochromate (C2H5)4NCrO3Cl is reported. The reaction has been carried out in aqueous acetic acid 50% (v/v) medium in presence of perchloric acid at constant ionic strength. The reaction has been found to be first order with respect to each of the oxidant and substrate under pseudo-first order conditions. The reaction is catalyzed by acid and follows a first order dependence on H+ concentration. The ionic strength variation has no effect on the reaction rate. The decrease in dielectric constant of the medium increases the rate of reaction. A 1 : 1 stoichiometry is observed in the oxidation and the reaction rate is not retarded by the addition of radical trapping agent acrylonitrile. The effect of temperature is studied and the various activation parameters are also determined. The products of oxidation are identified to be arabinose and formic acid. On the basis of observed facts, a hydride ion transfer mechanism is proposed.